Domination of Gender Relations in Qiraah Mubadalah - Kholifah Rahmawati; Heriyanto (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2025)
This paper examines the dominance of gender relations in the theory of Qira’ah Mubadalah, introduced by Faqihuddin Abdul Kodir as a hermeneutical method for interpreting religious texts based on the principle of reciprocity. In essence, Qira’ah Mubadalah is a universal approach, derived from Qur’anic verses that emphasize justice, equality, and partnership in social relations. However, in its practical application, the theory has been primarily focused on gender issues, particularly the relationship between men and women in both domestic and public spheres. This orientation is inseparable from the patriarchal culture and gendered nature of the Arabic language, as well as from Faqihuddin’s feminist perspective as its initiator. Employing a literature study, this research explores the ideas, principles, and application of Qira’ah Mubadalah and situates it within the framework of contemporary Qur’anic hermeneutics and feminist exegesis. The study finds that while Qira’ah Mubadalah significantly contributes to promoting more gender-just interpretations, its dominance in gender-related discourse makes it appear partial. Therefore, Qira’ah Mubadalah should be extended to a broader range of social relations in order to fully embody the Qur’an’s universal spirit.